Exploration of high-pressure processing (HPP) for preservation of the Swedish grown brown macroalgae Saccharina latissima - Jönsson, Madeleine; Allahgholi, Leila; Rayner, Marilyn; Nordberg Karlsson, Eva (Frontiers in Food Science and Technology, 2023)
Introducing seaweed to new food markets entails new challenges concerning efficient preservation. Hence, this study explores high-pressure processing (HPP) as an alternative technique to conventional methods by evaluating its effects on the composition, quality, and microbial safety of the Swedish grown macroalgae Saccharina latissima. The results from the physicochemical analysis showed that after high-pressure treatment the color was retained, while the algal texture was altered by up to an 87.7% reduction in hardness and a 60.0% reduction in compression. Biochemical analysis demonstrated some variations in the algal samples, but the nutritional content was overall retained after treatment. The microbial analysis showed a low microbial load of untreated fresh material, which was confirmed by a lack of amplification in polymerase chain reaction attempts and low growth during attempts on spontaneous proliferation using fresh and frozen algae. Additionally, shelf-life studies showed inconsistent growth, but overall, a low increase in unspecific bacteria, an increasing load of Enterobacteriaceae, no growth of Lactobacilli, and low fouling by mold and yeast. The results from this study can be useful in the continued attempts of introducing seaweed to new markets, with different prerequisites for post-harvest treatment.